Gilbert lectures on banking, 1957 : Unsecured advances - Mather L.C (London : Institute of Banker, 1957)
A survey of the general principles of lending a it applies particularly to unsecured advances.
Delivered under the auspices of the University of London King's College
obn 23/01/2019
Loans
Keywords: Banks and banking; Great Britain